Microstructural characterization of the A356 alloy in different processing routes used in the thixoforming process - Torres,Luis Vanderlei (2017)
ABSTRACT This work aims to evaluate different routes of raw material production to be used in thixoforming process. The semisolid materials exhibit particular structural characteristics, such the characteristic non dendritic structure. The studies for the production of near-net-shape parts have progressed together with the studies of material weight reduction on the automobile industries production lines. In general the advantages are energy saving, manufacturing steps reduction, productivity and quality increasing. Five processing routes have been investigated (conventional casting, electromagnetic stirring, grain refinement technique and different cooling rates) through microstructural characterizations, conventional metallographic and colour metallography. The material used in this study was the A356 alloy (commercial) having a hypoeutectic structure and grain size of about 750 μm and primary dendrite arm spacing size of around 80 μm, the combination of electromagnetic stirring + grain refining + high cooling rate provided the best route processing to obtain a refined structure, with grain sizes of around 240 μm, being feasible at the thixoforming process. Note also that using conventional metallography (black and white) all routes tested showed almost the same primary dendrite arm spacing size values ie had identical characteristics. Importantly, only with the characterization via polarized colour metallography is that was achieved in fact the best processing route definition.